Innenaufnahme eines Raumes der Ausstellung Neue Kunst in Afrika in Mainz (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1980)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Painting; Africa; Exhibitions; Interior decoration; Artists; Art Exhibition; Modern African Art; Mainz; Cultural Centre; Performing Arts Center